Enhanced atherosclerosis in apolipoprotein E knockout rabbits: role of apoB48-rich remnant lipoproteins - Niimi, Manabu; Chen, Yajie; Zhao, Huanyu; Tang, Xiangming; Matsuhisa, Fumikazu; Zhou, Huanjin; Yan, Haizhao; Chen, Lu; Kitajima, Shuji; Sato, Akira; Fan, Jianglin (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Apolipoprotein E (apoE) acts as a binding molecule for both the low-density lipoprotein receptor and the lipoprotein receptor-related protein and this function is essential for facilitating the hepatocyte uptake of lipoproteins containing apoB. The absence of apoE leads to increased atherogenicity in both humans and mice, although the precise molecular mechanisms remain incompletely understood.Objectives: This study aimed to investigate the susceptibility of apoE knockout (KO) rabbits, in comparison with wild-type (WT) rabbits, to diet-induced hyperlipidemia and atherosclerosis.Methods: ApoE KO rabbits and WT rabbits were fed a diet containing 0.3% cholesterol for 16 weeks. Plasma lipid levels, lipoproteins, and apolipoproteins were analyzed. Atherosclerosis was evaluated at the endpoint of experiments.In addition, we evaluated the oxidizability of those lipoproteins containing apoB to investigate the possible mechanisms of atherosclerosis.Results: Male apoE KO rabbits showed significantly elevated levels of total cholesterol (TC) and triglycerides compared to control rabbits, while female apoE KO rabbits displayed similar high TC levels, albeit with significantly higher triglyceride levels than WT controls. Notably, both male (2.1-fold increase) and female (1.6-fold increase) apoE KO rabbits exhibited a significantly augmented aortic lesion area compared to WT controls.Pathological examination showed that the increased intimal lesions in apoE KO rabbits were featured by heightened infiltration of macrophages (2.7-fold increase) and smooth muscle cells (2.5-fold increase). Furthermore, coronary atherosclerotic lesions were also increased by 1.8-fold in apoE KO rabbits.Lipoprotein analysis revealed that apoB48-rich beta-very-low-density lipoproteins were notably abundant in apoE KO rabbits, suggesting that these remnant lipoproteins of intestinal origin serve as the primary atherogenic lipoproteins. Moreover, apoB48-rich remnant lipoproteins isolated from apoE KO rabbits exhibited heightened susceptibility to copper-induced oxidation.The findings indicate that apoB48-rich remnant lipoproteins, resulting from apoE deficiency, possess greater atherogenic potential than apoB100-rich remnant lipoproteins, regardless of plasma TC levels.